"Es que tú eres una changa": stigma experiences among Latina women living with endometriosis. (2nd January 2021) - Matías-González, Yatzmeli; Sánchez-Galarza, Astrid N.; Flores-Caldera, Idhaliz; Rivera-Segarra, Eliut
Abstract: Introduction: Endometriosis is a chronic inflammatory gynecologic disease affecting 5–10% of women of reproductive age of all ethnicities. Symptoms of this painful condition impact the physical, mental health, and quality of life of patients. Stigma is a social determinant of health documented to negatively impact people living with chronic conditions and have been associated with social exclusion, high levels of stress, and interference with medical care. The purpose of this study was to document stigma experiences among Latina women living with endometriosis. Methods: A qualitative design using focus groups was implemented. Thematic analysis was conducted for data interpretation. A total of 50 women participated in five focus groups. Results: The main theme " changuería " emerged as a label applied across multiple contexts and interactions in the lives of participants, suggesting that stigmatization is an ever-present barrier among women living with endometriosis. Participants reported that relatives, partners and health professionals perceive pain during menstruation as something women should be able to manage, producing a sense of inability to disclose the extent of suffering. Conclusion: These results highlight the importance of addressing stigma as a way to foster healthcare seeking and minimize its impact on physical, mental health, and wellbeing.